Experimental characterization of the mechanical behaviour and the failure of multi-sheet and multi-material spot welded assembly. (August 2019) - Tounsi, R.; Haugou, G.; Chaari, F.; Leconte, N.; Markiewicz, E.
Highlights: Mechanical behaviour of three-sheet multi-material spot welded assembly. Pure opening mode, pure shear mode and mixed opening/shear mode. A significant effect of the loading angle on the mechanical behaviour. A pronounced effect of nugget diameter size on the ultimate force and the dissipated energy. Abstract: An experimental investigation of the mechanical behaviour of three-sheet multi-material spot welded assembly is performed. An experimental device based on the Arcan principle is developed to test the three-sheet spot welded specimen under pure opening mode, pure shear mode and mixed opening/shear mode with three nugget sizes. A significant effect of the loading angle is reported and explained by three identified failure modes as a pull-out failure mode (pure opening), an inter-facial failure mode (pure shear) and a mixed pull-out/inter-facial failure mode (mixed opening/shear). A pronounced effect of nugget diameter size is reported on the ultimate force and the dissipated energy. A preliminary study of the strain-rate sensitivity of the three-sheet multi-material spot welded assembly is also undertaken.